ETOS SOSIAL MASYARAKAT BELITUNG DALAM NOVEL SIRKUS POHON KARYA ANDREA HIRATA ( KAJIAN SOSIOLOGI SASTRA ) - Wahida, Dinda Nahdlotul; Yanuarsih, Sri; Letreng, I Wayan (Universitas Tanjungpura, 2024)
Social ethos of society is the integrity of the most influential values on a particular people, especially in human behavior. The purpose of this study is to obtain detailed knowledge about the negative aspects in social form, based on the realities in Indonesian society, which can be presented and described through the three aspects of social ethos based on Max Scheler's theory: (1) poverty, (2) ignorance, and (3) ineffectual education. The subject of this study is the novel